Anodic Formation of Self-Organized Cobalt Oxide Nanoporous Layers - Lee, Chong-Yong; Lee, Kiyoung; Schmuki, Patrik (Angewandte Chemie International Edition, 2013)
High-aspect-ratio, ordered porous Co3O4 layers were formed by self-organizing anodization of a cobalt substrate and subsequent annealing. The key for successful formation of such layers is to sufficiently suppress competing oxygen evolution during anodization. The aligned Co3O4 channel layers behave as a highly efficient water oxidation catalyst.
EAM Import::2019-03-13